„Atgimimo banga“ Challenge to Soviet Mass media: Reform Movement of Lithuania (Sąjūdis) Telecast as „Open Protest Field“ in Time of Political Changes (1988 June– 1990 March) - Vaitelė, Tomas (Žurnalistikos tyrimai, 2021)
During the Soviet occupation, the whole Lithuanian SSR media was regarded as one of the key propaganda tools based on pure ideological content and socialist-communist messages. In such a media setting television played an essential role; together with radio (as in Moscow’s example) the latter felt under control of a committee ruled by the Council of Ministers (CM), Central Committee (CC) and Moscow patrons itself. But this situation was about to change when Sąjūdis (Reform Movement of Lithuania) came to public and tried to established its right to uncensored broadcast time via television for its own dissemination of information, which sometimes had a strong political message and was not in favour of ruling regime and party. Sąjūdis had a purpose which was totally new during Lithuanian SSR times since the start of television broadcasts in 1957 – it was uncensored broadcasting time. Based on archive sources, memoirs and press articles, this research focuses on the telecast “Atgimimo banga“ as one of the essential informational channels for Sąjūdis. This article tries to disclose its history, influence and conflicts between Sąjūdis and ruling regime, which tried to control and censor telecast’s content. Eventually, the sporadic telecast’s format had another effect: when in 1989 Sąjūdis became important part of the Lithuanian SSR political system, telecast’s popularity came to decline. One of the most popular perestroika time TV programs had some unfulfilled expectations, and, during the time, it made it as one of the most unpopular. The chronological boundaries of this research start at June of 1988, when Sąjūdis was created, and ends in March of 1990, when Lithuania declared its independence from Soviet Union.
Keywords: Sąjūdis; Reform Movement of Lithuania; censorship; television; mass media; Lithuanian communist party; Atgimimo banga; Glasnost; Perestroika